TEACHING SPEAKING BY USING MAKE A MATCH TECHNIQUE FOR JUNIOR HIGH SCHOOL STUDENTS - Yetti Kurnia; Rusdi Rusdi (Journal of English Language Teaching, 2017)
Speaking is one of the most difficult skills in learning English. Therefore, students need daily practices either inside or outside the classroom to make students fluent in speaking. This paper describes how to use Make a Match techniques in teaching of speaking to junior high school students.Make a Match technique is one of technique that can be used by teachers in teaching English especially speaking because Make a Match is a kind of techniques in the form of a game that will make students feel happy and can build motivation to learn. In addition, this technique can increase students’ interest in learning speaking skills because Make a Match is a technique of looking for a partner using the card and picture as well as the award of prizes to the winners.